Facile, Energy‐Efficient Microscale Fibrillation of Polyacrylamides under Ambient Conditions. Issue 23 (1st May 2022) - Cruz, Menandro V.; Shah, Darshil U.; Warner, Nina C.; McCune, Jade A.; Scherman, Oren A.
Abstract: Insight into fiber formation can provide new rationale for the design and preparation of fibers with programmed mechanical properties. While synthetic bioinspired fibers have shown impressive tensile properties, the fiber formation process remains poorly understood. Moreover, these systems are highly complex and their formation is environmentally and economically costly. Controlled fiber formation under ambient conditions from polyacrylamide solutions with properties comparable to natural fibers such as wool and coir is demonstrated. Photopolymerization and subsequent microscale fibrillation of different acrylamides in water/ethanol mixtures yield a simple and energy‐efficient route to fiber formation. This strategy reduces required processing energy by two‐to‐three orders of magnitude. Through extensive experimental elucidation, insight into precise fiber forming conditions of polymeric solutions is achieved. Ethanol is utilized as a chain transfer agent to control the molecular weight of the polyacrylamides, and the entanglement regimes of the solutions are determined through rheological characterization showing fiber formation above the entanglement concentration. Unique from previously reported hydrogel microfibers, it is shown that fibers with good mechanical properties can be obtained without the need for composites or crosslinkers. The reported approach offers a platform for fiber formation under ambient conditions with molecular‐level understanding of their assembly. Abstract : Insight into fiber formation can provide rationale for the design of fibers with programmed mechanical properties. An energy‐efficient route to formation of fibers with properties comparable to natural fibers such as wool and coir is reported. This strategy offers a molecular‐level understanding of fiber formation under ambient conditions which reduces current required processing energy by two‐to‐three orders of magnitude.